RANCANG BANGUN SISTEM INFORMASI HASIL UJI COBA UJIAN NASIONAL SMA SE-KABUPATEN PEKALONGAN BERBASIS WEB MENGGUNAKAN PHP DAN MYSQL - Imam Rosyadi; Tri PAngestiyani (Universitas Muhammadiyah Pekajangan Pekalongan, 2016)
The National Exam is a graduation requirement that students have to take the given subject . To deal with implementing School National Exam Tests to measure the extent to which the ability of students . In this case the information delivered to student results manually according maple teacher tested resulting in difficulty in conveying information on the results of the National Exam Tests. In the process of data collection in order to solve the problem , the authors use the method of data collection by literature studies , interviews , and gathered documents . And for designing software applications , the authors use the waterfall development method . Application information system test results are made with the web-based programming languages PHP and MySQL as database . Based on the results of the testing that has been done , application of Information Systems of the National Examination Test results are expected to assist in conveying information MKKS Trial results . Keywords : National Examination test results , waterfall , PHP , MySQL ABSTRAKSI Ujian Nasional merupakan sebagai syarat lulus bahwa siswa tersebut telah menempuh mata pelajaran yang diberikan. Untuk menghadapinya Sekolah melaksanakan Ujicoba Ujian Nasional untuk mengukur sejauh mana kemampuan siswanya. Dalam hal ini informasi hasil tersebut disampaikan kepada siswa secara manual sesuai guru mapel yang diujikan sehingga terjadi kesulitan dalam menyampaikan informasi hasil Ujicoba Ujian Nasional tersebut. Pada proses pengumpulan data dengan tujuan untuk memecahkan masalah, penulis menggunakan metode pengumpulan data dengan cara studi literatur, wawancara, dan mengumpulkan dokumen. Dan untuk merancang aplikasi perangkat lunaknya, penulis menggunakan metode pengembangan waterfall. Aplikasi sistem informasi hasil ujicoba ini dibuat dengan bahasa pemrograman berbasis web PHP dan MySQL sebagai database. Berdasarkan dari hasil pengujian yang telah dilakukan, aplikasi Sistem Informasi Hasil Ujicoba Ujian Nasional ini diharapkan dapat membantu pihak MKKS dalam menyampaikan informasi hasil Ujicoba. kata Kunci : hasil ujicoba Ujian Nasional, waterfall, PHP, MySQL